PROSEDUR TATA KELOLA ADMINISTRASI PENJUALAN E-COMMERCE DI PT. VOLANS - Sugiyono Sugiyono; Evi Okli Lailani; Nurul Khomariyati (ITB Swadharma, 2021)
In the current era of technology, many things have been made easier with technology. Digital developments in Indonesia are also inseparable from the role of the community currently in social media which has an impact on people's dependence on the internet. The internet has become a connecting tool between us and the digital world. With the internet, all digital things can be mastered in the palm of your hand. For example, watching TV series and movies can be accessed via Smartphones, office meetings or meetings can also be done through virtual meetings, even in terms of shopping, we have been facilitated by several modern digital markets known as e-commerce where we don't waste time and energy. , we can shop efficiently. PT. Volans is engaged in selling running shoe brands that focus more on its target in digital sales or also known as ECommerce. The problem in this research is to find out how the E-Commerce Sales Administration Governance Procedure is applied at PT. Volans.